The cook of the Halcyon - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery., 2021)
"The new novel in the transporting New York Times bestselling Inspector Montalbano mystery series. Two deaths, the suicide a newly laid-off worker and an unscrupulous businessman found murdered, leads Inspector Montalbano to inspect the Halcyon, a nearly abandoned mysterious ship with no passengers. CONTINUES TO HOOK NEW READERS: Each book is a welcome invitation for new readers to the ever popular and growing series. IMPRESSIVE SALES TRACK: Five of the Montalbano books have hit the New York Times bestseller list and the series continues to reorder and bring in consistent sales with each new book. We have sold over 700,000 Montalbano books in all formats. Camilleri continues to be a mega-bestseller in Italy. Today, the Inspector Montalbano series has sold over 10 million copies worldwide, and has been translated into over 32 languages. ESCAPE INTO SICILY: Camilleri's Inspector Montalbano series has always been greatly praised for its atmospheric, sensual descriptions of Sicily, with its cool beaches and rustic delicacies, it's pure escapism"--